Antibacterial activity of diff erent solvent extracts of Caulerpa chemnitzia (Esper) J.V. Lamououx, from Mandapam, Gulf of Mannar Southeast Coast, Tamil Nadu, India - S. Krishnamoorthy, V. Venkatesalu, G. Adaikala Raj, M. Chandrasekaran (Journal of Medicinal Herbs and Ethnomedicine, 2015)
Phytochemical analyses and in vitro antibacterial activity of different extracts of hexane, chloroform, ethyl acetate, acetone, and methanol extracts of green algae, Caulerpa chemnitzia (Esper) J.V. Lamououx, against Bacillus subtilis, Streptococcus pyogenes, Escherichia coli, Klebsiella pneumoniae, Proteus mirabilis, Proteus vulgaris, Pseudomonas aeruginosa, Salmonella typhimurium, Shigella flexneri, and Vibrio cholerae. The extent of the inhibitory zone, Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) were determined. The ethyl acetate extract of C. chemnitzia showed the presence of phytochemicals, terpenoids, tannins and phenolic compounds strongly than the other solvent extracts. The mean zone of inhibition produced by the extracts in agar diffusion assays against the tested bacterial strains ranged from 7.1 to 13.6 mm. The MIC was between 125 and 500 Î¼g/mL while the MBC were between 250 and 1000 Î¼g/mL. The highest mean zone of inhibition (13.6 mm) and the lowest MIC (125 Î¼g/mL) and MBC (250 Î¼g/mL) values were observed in ethyl acetate extract against B. subtilis. These findings suggest that the ethyl acetate extract of C. chemnitzia can be used as an antibacterial substance for the treatment of bacteria causing acquired infection.